Manfaat Program Lisan Arab Bagi Mahasiswa Pendidikan Bahasa Arab Universitas Pendidikan Indonesia - Aisyah Miftahusy Syahidah Al Firdausy; Nadya Diena Mumtazah; Saviola Arya Bramantya; Siti Nurrahmi Fahira; Ahmad Fu’adin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study discusses the benefits of the Arabic oral program for Arabic Language Education students at the Indonesian University of Education. This study aims to provide an overview and add insight to the reader towards one of the effective Arabic language learning methods. In addition, this study aims to examine the benefits of the Arabic language learning program based on the community learning method factually from the point of view of the participants of the Lisan Arab program. In this research, the causal-comparative method with a qualitative-descriptive approach was used, and the data collection technique used a purposive sampling method through a questionnaire filled with 36 respondents of Arabic Language Education students at the Indonesian University of Education. The results showed that the Arabic Oral program is beneficial and influential for Arabic Language Education students who need a basic knowledge of Arabic. This benefit is due to developing Arabic language skills in the Oral Arabic program.